A novel damage identification method for flue gas turbine blades based on tip timing. (April 2023) - Zhang, Fengli; Yu, Haotian; Wang, Jinjiang
Abstract: Tip timing signal analysis has been applied to the online condition monitoring of high-speed blades. However, traditional tip timing analysis methods are not suitable for low-speed flue gas turbines. Therefore, this paper proposes a novel blade tip timing signal analysis method based on an investigation of the dynamic response characteristics of low-speed blades. First, the finite element modal theory is introduced to analyze the characteristics of blade damage. Second, an equivalent cantilever beam analysis model of flue gas turbine blades is established under complex environment and working conditions. In order to monitor the variation of local stiffness, a damage identification method based on the variation of the free end deflection of the equivalent cantilever beam is proposed. Finally, a rotating blade tip timing monitoring testing rig is established to verify the feasibility of the proposed method. The results show that the cracks originating at about 80% of the blade height have the greatest influence on blade stiffness, followed by blade root. The calculated blade damage parameters are 4.8464 mm and 3.7588 mm, and the crack influencing factors are 4.7476 and 3.6822, respectively, indicating that the change trend is consistent with the blade damage rules. Highlights: A novel blade tip timing signal analysis method for low-speed blades. Build an equivalent cantilever beam model of flue gas turbine blades. Finite element modeling of a FGT blade to study the damage characteristics.